HUBUNGAN PENGETAHUAN IBU DENGAN STATUS KEBERSIHAN GIGI DAN MULUT PADA ANAK UMUR 3-5 TAHUN GAMPONG PEUNITI KOTA BANDA ACEH - Reca Reca; Elfi Zahara (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2022)
Mothers have a role in preventing plaque accumulation in children. Based on initial data obtained from interviews with 10 mothers with children aged 3-5 years in Peuniti Village, 60% of mothers still lack knowledge in maintaining children's dental hygiene. Based on the dental hygiene examination, the 10 children examined on average had dental hygiene status with a score of 40 bad categories so that there was a gap between the targets set by the government. This study aims to determine the relationship between mother's knowledge and the dental hygiene status of children aged 3-5 years in Peuniti Village. This research is analytic with a cross sectional study approach. Sampling using total sampling, namely all children aged 3-5 years and their mothers as respondents amounted to 49 people in Peuniti Village. The research instrument used a questionnaire and a diagnostic set. Data analysis used Chi-Square statistical test. The results showed that from 49 mothers, 15 people (30.6%) had poor knowledge with the results of dental hygiene examinations in very poor categories, 18 children (36.7%) with chi-square test results p value = 0.005. It can be concluded that there is a significant relationship between maternal knowledge and dental hygiene status. It is recommended to mothers to be able to improve their child's dental care by seeking information through mass media and electronic media and conducting regular dental check- ups